2020
DOI: 10.1142/s2047684120500128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dynamic temperature variation and inplane varying loads over post-buckling and free vibration analysis of sandwich composite beam

Abstract: In this study, nonlinear post-buckling and free vibration analysis of shape memory polymer sandwich composite (SMPSC) under dynamic temperature variation is performed. For the analysis, simplified Co continuity based on higher-order shear deformation theory (HSDT) has been adopted to perform finite element analysis (FEA). Numerical solutions are obtained by iterative Newton–Raphson method considering Von-Karman nonlinear kinematics. Material properties of SMPSC, with Shape Memory Polymer (SMP) as matrix and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Huang and Tauchert [24] examined composite laminates under uniform temperature distributions and determined the critical buckling temperature and compared the exact solution outcomes with that comes from finite element results. Lal and Markad [25] investigated shape memory polymer composite sandwich beams under thermo-mechanical loading and determined the influence of various parameters on the buckling load and nondimensional frequencies. Shiau et al [26] investigated the influence of modulus ratio, thermal expansion coefficient ratio, aspect ratio, and fibre angle on the mode shape of composite laminates subjected to thermal loading and observed that laminates with higher modulus and thermal expansion ratio show higher thermal buckling mode shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Tauchert [24] examined composite laminates under uniform temperature distributions and determined the critical buckling temperature and compared the exact solution outcomes with that comes from finite element results. Lal and Markad [25] investigated shape memory polymer composite sandwich beams under thermo-mechanical loading and determined the influence of various parameters on the buckling load and nondimensional frequencies. Shiau et al [26] investigated the influence of modulus ratio, thermal expansion coefficient ratio, aspect ratio, and fibre angle on the mode shape of composite laminates subjected to thermal loading and observed that laminates with higher modulus and thermal expansion ratio show higher thermal buckling mode shapes.…”
Section: Introductionmentioning
confidence: 99%
“…(Mathieson and Fam, 2014; Sharaf and Fam, 2011) Chose sandwich panels made from polymer shells reinforced with fiber glass and polyurethane foam cores and then exposed them to large-scale off-loading and reverse loading. (Lal and Markad, 2020a, 2021b) Examined thermal analysis and nonlinear post-buckling and free vibration analysis of smart and polymer sandwich plates shape memory alloy under uniform temperature and dynamic temperature changes. (Lal and Markad, 2020b, 2021a) Examined Nonlinear post-buckling analysis sandwich composite beams subjected to static load and they also examined nonlinear flexural analysis of carbon nanotube-reinforced sandwich beams under dynamic loading.…”
Section: Introductionmentioning
confidence: 99%
“…Sandwich composites made from high performance fibre laminate faces over foam cores are highly used in aerospace, naval applications and wind turbines where the weight is critical (Carlsson and Kardomateas, 2011; Lal and Markad, 2020a, 2020b; Selver and Kaya, 2019b). The core part plays critical role to provide compressive strength to sandwich composites whilst it is weaker than face or skin materials (Thomsen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%